-(-2v-6)=-3-5(v+8)

Simple and best practice solution for -(-2v-6)=-3-5(v+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-2v-6)=-3-5(v+8) equation:


Simplifying
-1(-2v + -6) = -3 + -5(v + 8)

Reorder the terms:
-1(-6 + -2v) = -3 + -5(v + 8)
(-6 * -1 + -2v * -1) = -3 + -5(v + 8)
(6 + 2v) = -3 + -5(v + 8)

Reorder the terms:
6 + 2v = -3 + -5(8 + v)
6 + 2v = -3 + (8 * -5 + v * -5)
6 + 2v = -3 + (-40 + -5v)

Combine like terms: -3 + -40 = -43
6 + 2v = -43 + -5v

Solving
6 + 2v = -43 + -5v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '5v' to each side of the equation.
6 + 2v + 5v = -43 + -5v + 5v

Combine like terms: 2v + 5v = 7v
6 + 7v = -43 + -5v + 5v

Combine like terms: -5v + 5v = 0
6 + 7v = -43 + 0
6 + 7v = -43

Add '-6' to each side of the equation.
6 + -6 + 7v = -43 + -6

Combine like terms: 6 + -6 = 0
0 + 7v = -43 + -6
7v = -43 + -6

Combine like terms: -43 + -6 = -49
7v = -49

Divide each side by '7'.
v = -7

Simplifying
v = -7

See similar equations:

| -2(8u-7)+4u=2(u+6) | | 2/3(x-6)-1/3(x-3) | | -2(8u-7)+4v=2(v+6) | | 2w^3+6w^2-4w=0 | | 90d=2 | | -(3-3n)=4(7+2n)+4 | | 81+2d= | | -2n+8(n-7)=-86 | | 6a^3-12a^2+14a=0 | | -3(2-1)=12 | | -2n+8(n-7)=-3-5(v+8) | | 18=69-24 | | L=b+c-dsolvec | | 10w+10+3w=6(9+w)-14 | | 8+7n-6-4n=n-8 | | (2x^2-13x+6)/(6x^2-x-1) | | 8x-9=41 | | 3m(m+4)=18 | | 6x-3=7x-10 | | 1/3(3x-2)=6-x | | 2n+3+8=1 | | 31.83D=5103 | | 1=1+n-1 | | -3y+2x=6 | | 2a-7=-2a+5 | | 291-13-8= | | 0=-4b-6b | | 291-(-13-8)= | | 291-(-13+-8)= | | r/4-7/4+3r/4=1/4 | | -7(3+v)=-77 | | s/5=-16 |

Equations solver categories